HipHop interacts with HOAP and HP1 to protect Drosophila telomeres in a sequence-independent manner. - Gao, G.; Walser, J.C.; Beaucher, M.L.; Morciano, P.; Wesolowska, N.; Chen, J.; Rong, Y.S. (The EMBO Journal, 2010)
Telomeres prevent chromosome ends from being repaired as double-strand breaks (DSBs). Telomere identity in Drosophila is determined epigenetically with no sequence either necessary or sufficient. To better understand this sequence-independent capping mechanism, we isolated proteins that interact with the HP1/ORC-associated protein (HOAP) capping protein, and identified HipHop as a subunit of the complex. Loss of one protein destabilizes the other and renders telomeres susceptible to fusion. Both HipHop and HOAP are enriched at telomeres, where they also interact with the conserved HP1 protein. We developed a model telomere lacking repetitive sequences to study the distribution of HipHop, HOAP and HP1 using chromatin immunoprecipitation (ChIP). We discovered that they occupy a broad region >10 kb from the chromosome end and their binding is independent of the underlying DNA sequence. HipHop and HOAP are both rapidly evolving proteins yet their telomeric deposition is under the control of the conserved ATM and Mre11-Rad50-Nbs (MRN) proteins that modulate DNA structures at telomeres and at DSBs. Our characterization of HipHop and HOAP reveals functional analogies between the Drosophila proteins and subunits of the yeast and mammalian capping complexes, implicating conservation in epigenetic capping mechanisms.